The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1002/(sici)1097-461x(1996)58:5<497::aid-qua7>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional crystal orbital calculations on mononucleotide crystallohydrates. I. Sodium mononucleotide crystallohydrates

Abstract: rnCrystal-orbital calculations on the three-dimensional disodium deoxyguanosine-5'-monophosphate tetrahydrate, disodium uridine-3'-monophosphate tetrahydrate, monosodium monoprotonated deoxyadenosine-5' monophosphate hexahydrate, and disodium deoxycytidine-5'-monophosphate heptahydrate crystallohydrates were carried out in a Hartree-Fock all-valence-electron approximation using the CRYSTAL92 routine package. The first, the second, and the last compounds were found to be insulators, whereas the third one should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…As concerns the problem of impurity levels due to DNA hydration shells, a serious caution should be made, since earlier systematical studies have shown that the onset of such impurity levels might also be dependent on the AO basis set used. [17][18][19][20][21][22][23] With all this in mind, the following question arises: Could DNA watercounterion hydration shell play a direct role in DNA charge transfer/transport processes, that is, be capable of providing specific electron/hole transmission channels, in addition to the approved ones formed by the overlapping π-orbitals in DNA basepair stacks? Asking such a question is absolutely justified, especially in view of the experimental results published in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…As concerns the problem of impurity levels due to DNA hydration shells, a serious caution should be made, since earlier systematical studies have shown that the onset of such impurity levels might also be dependent on the AO basis set used. [17][18][19][20][21][22][23] With all this in mind, the following question arises: Could DNA watercounterion hydration shell play a direct role in DNA charge transfer/transport processes, that is, be capable of providing specific electron/hole transmission channels, in addition to the approved ones formed by the overlapping π-orbitals in DNA basepair stacks? Asking such a question is absolutely justified, especially in view of the experimental results published in Ref.…”
Section: Introductionmentioning
confidence: 99%